A hidden urinary bladder diverticular tumour: a diagnostic challenge - Che Mohamed, Siti Kamariah; Kamarulzaman, Mohd Nazli; Ghazali, Hamid (Ministry of Health and Universiti Brunei Darussalem, 2015)
Urinary bladder diverticulum tumour is rare. It has been estimated that only 2.6% of all bladder diverticulum develop malignancy and most were diagnosed late. Delay in diagnosis can be due to presence of intra-diverticular stone which can compress and hide any evidence of mucosal changes. We report the case of a 53-year-old man who presented with multiple lower urinary tract stone including in the urethra, bladder and bladder diverticulum. Serial investigations before a diagnosis of a bladder diverticulum adenocarcinoma were made. The tumour was hidden behind a stone.